Information and communications security : 16th International Conference, ICICS 2014, Hong Kong, China, December 16-17, 2014, Revised selected papers /: 16th International Conference, ICICS 2014, Hong Kong, China, December 16-17, 2014, Revised selected papers. (2015) - Unknown
No abstract available